Continuous Flow Biocatalytic Reductive Amination by Co‐Entrapping Dehydrogenases with Agarose Gel in a 3D‐Printed Mould Reactor. (26th October 2022) - Croci, Federico; Vilím, Jan; Adamopoulou, Theodora; Tseliou, Vasilis; Schoenmakers, Peter J.; Knaus, Tanja; Mutti, Francesco G.
Abstract: Herein, we show how the merge of biocatalysis with flow chemistry aided by 3D‐printing technologies can facilitate organic synthesis. This concept was exemplified for the reductive amination of benzaldehyde catalysed by co‐immobilised amine dehydrogenase and formate dehydrogenase in a continuous flow micro‐reactor. For this purpose, we investigated enzyme co‐immobilisation by covalent binding, or ion‐affinity binding, or entrapment. Entrapment in an agarose hydrogel turned out to be the most promising solution for this biocatalytic reaction. Therefore, we developed a scalable and customisable approach whereby an agarose hydrogel containing the co‐entrapped dehydrogenases was cast in a 3D‐printed mould. The reactor was applied to the reductive amination of benzaldehyde in continuous flow over 120 h and afforded 47 % analytical yield and a space‐time yield of 7.4 g L day −1 using 0.03 mol% biocatalysts loading. This work also exemplifies how rapid prototyping of enzymatic reactions in flow can be achieved through 3D‐printing technology. Abstract : A customisable approach, whereby an agarose hydrogel containing co‐entrapped dehydrogenases was cast in a 3D‐printed mould, was developed. The reactor was applied to the reductive amination of benzaldehyde in continuous flow over 120 h (space‐time‐yield 7.4 g L −1  day −1, 0.03 mol% biocatalysts loading). This work also shows how 3D‐printing technology can accelerate prototyping of enzymatic reactions in flow.